STRATEGI PENGENDALIAN KUALITAS PRODUK BUMBU TABUR MENGGUNAKAN METODE TAGUCHI - Kristanto , Dwi; Nur Fitriyani, Diyah (Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Cilacap, 2023)
The high defect rate in the powdered seasoning product produced at PT ABC serves as the main reason for this research. The study aims to determine the factors influencing the quality of the seasoning product using the Taguchi method. The analysis conducted identified two levels and three significant factors. These factors include the number of briefing sessions for operators, the intensity of packing machine maintenance, and the determination of sample size in quality control. After experimentation, this research concludes that the optimal conditions for seasoning production involve conducting two briefing sessions for operators, performing machine packing maintenance twice, and taking quality control samples 332 times. The use of 332 samples is based on the minimum sample size required using a statistical approach with a 95% confidence level. The analysis results indicate that machine maintenance has the greatest impact on the quality of the seasoning product, contributing approximately 23.02% at the first level. The number of operator briefings contributes about 7.91% at the second level, while quality control contributes approximately 5.62% at the second level. This research highlights the importance of considering the number of operators briefing sessions, the frequency of packing machine maintenance, and the method used to determine the sample size in quality control when producing seasoning products. By applying the Taguchi method, it is possible to identify the optimal levels for these three factors to produce high-quality seasoning products.